Intersectionalities of Gender Violence: Legal Remedies: Editorial - Goldscheid, Julie (Oñati Socio-Legal Series, 2015)
Critiques of legal remedies’ capacity adequately to address the intersectional nature of gender violence lie at the heart of both theoretical and practical discourse. Concern about remedies complements the important literature detailing the narrative experiences of those who experience violence grounded in multiple intersections of identity. This is an introduction to a set of papers that represent highlights from the conference entitled “International Congress on Gender Violence: Intersectionalities”. The papers address approaches to legal remedies that take into account the intersectional nature of gender violence. Las críticas a la capacidad de los remedies legales para abordar la naturaleza interseccional de la violencia de género están en el centro del discurso teórico y práctico. La preocupación sobre los remedios complementa la importante literatura que detalla las experiencias narrativas de las personas que experimentan violencia alojada en múltiples intersecciones de identidad. Esta es una introducción a artículos representativos del Congreso Internacional sobre Violencia de Género: Intersecciones. Los artículos abordan un acercamiento a los remedios legales que tienen en cuenta la naturaleza interseccional de la violencia de género. DOWNLOAD THIS PAPER FROM SSRN: http://ssrn.com/abstract=2710535